EXPLORING THE IMPACT OF AI-CHATGPT ON CREATIVITY SKILLS OF POSTGRADUATE STUDENTS AT KUST KOHAT - Shakeel Nawaz; Prof. Dr. Naseer ud Din*; Abdul Wahab (`, 2025)
This research explores how AI-ChatGPT influences creativity skills at the higher level of thinking among the postgraduate students at Kohat University of Science and Technology (KUST) Kohat. The study examines the connection between AI-ChatGPT as an independent variable and the creativity skills measured as a dependent variable. These include originality, flexibility, innovation and problem-solving etc. A standardized adapted questionnaire applied to gather data from 150 postgraduate students who underwent regression and correlation analysis with SPSS statistical analysis. AI-ChatGPT usage demonstrated positive effects on creativity skills in students because they developed improved concepts and conceptually innovative approaches. Findings show that AI generates challenges in student creative abilities through AI over usage since dependence on AI interferes with students’ ability to think independently. The research outcomes present essential knowledge to educational leaders and policy makers about implementing AI tool integration successfully to develop creative capabilities in graduate studies. Keywords: AI-ChatGPT, higher-order thinking, creativity skills.